2006
DOI: 10.1038/sj.ijo.0803356
|View full text |Cite
|
Sign up to set email alerts
|

The G1057D polymorphism of IRS-2 gene and its relationship with obesity in conferring susceptibility to type 2 diabetes in Asian Indians

Abstract: Objective: To investigate the association of insulin receptor substrate-2 (IRS-2) G1057D polymorphism with type 2 diabetes and obesity in Asian Indians. Methods: The study comprised of 1193 normal glucose tolerant (NGT) subjects and 1018 subjects with type 2 diabetes, aged X20 years with an average body mass index of 23.774.6 and 25.374.2 kg/m 2 , respectively. The subjects were unrelated and randomly selected from the Chennai Urban Rural Epidemiology Study (CURES), a population-based study in Chennai in south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 31 publications
3
30
1
1
Order By: Relevance
“…Additionally there are some inconsistent results about association between IRS2 haplotypes and obesity risk (Lautier et al, 2003). Some previous studies conducted to investigate the effect of IGF-I, INSR and IRS2 gene polymorphisms on insulin resistant and type 2 diabetes mellitus (FloresMartínez et al, 2004;Bodhini et al, 2007;Vella et al, 2008;Baroudi Ouederni et al, 2009;Malodobra et al, 2011). So far, the associations of insulin pathway gene polymorphisms with prostate and breast cancer have been studied intensively but their results were inconsistent (Ho et al, 2003;Neuhausen et al, 2005;Deming et al, 2007;Deming et al, 2008;Sarma et al, 2008;Xuefen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally there are some inconsistent results about association between IRS2 haplotypes and obesity risk (Lautier et al, 2003). Some previous studies conducted to investigate the effect of IGF-I, INSR and IRS2 gene polymorphisms on insulin resistant and type 2 diabetes mellitus (FloresMartínez et al, 2004;Bodhini et al, 2007;Vella et al, 2008;Baroudi Ouederni et al, 2009;Malodobra et al, 2011). So far, the associations of insulin pathway gene polymorphisms with prostate and breast cancer have been studied intensively but their results were inconsistent (Ho et al, 2003;Neuhausen et al, 2005;Deming et al, 2007;Deming et al, 2008;Sarma et al, 2008;Xuefen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The CETP and APOE polymorphisms failed to show association with T2DM, while D442G polymorphism of CETP was not traced in either cases or controls of North Indian population [92]. The IRS2 G1024D polymorphism was only studied in Chennai population [96], was found to increase the susceptibility to type 2 diabetes in conjunction with obesity.…”
Section: Genetic Studies In Indiamentioning
confidence: 95%
“…We have furnished results of these Indian studies in Table 5, which suggest strong role of common variants of T2DM susceptible genes such as TCF7L2, [40,41,138,139,142] PPARG [64,139,142] and CAPN10 [57,58] and some rare variants of genes such as LPL [69], ENPP1 (PC-1) [75], FTO [94,139], IRS-2 [96], PGC-1γ [84,85] and IL-4 & ILRN1 [98].The replicative studies of GWAS also show strong association of KCNJ11, [142] IGF2BP2, [139,142] CDKAL1, [142] SLC30A8 [142], CDKN2A [142,144], HHEX [142,143], CDKN2A/B, [143] and BAZ1 [143]. Of all the genes studied so far, TCF7L2 variants studied so far in the Indian populations (including the migrant Indians from UK [47]) show most significant and consistent association with T2DM, except for rs7901695 and rs12235572 [138].…”
Section: Genetic Studies In Indiamentioning
confidence: 98%
“…Several candidate studies in individuals of South Asian ancestry have replicated associations identified in other ethnicities [105]. These include signals such as FTO, IRS2, APOB, and UCP3 with waist circumference, BMI, and waist to hip ratio, as well as interactions with diabetes [106][107][108][109][110][111]. Lastly, genetic investigations in Aboriginal people have mostly been underpowered to replicate a majority of signals.…”
mentioning
confidence: 98%